Implementasi dan Efektivitas Game Edukatif Terhadap Anak Tunarungu di TPQ As-Sakinah - Nida Fadhila Safitri; Sabrina Ais Zahra; Alis Kholisoh; Badrani Dhyal Haqqi; Ferida Rahmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Learning for deaf children requires media that suits the characteristics of visual learning so that the material can be understood more effectively. One innovation that can be implemented is the use of educational games as an interactive and fun learning medium. This study aims to describe the implementation and analyze the effectiveness of an educational game of guessing the hijaiyah letters in the learning of deaf children at TPQ As-Sakinah. The study used a qualitative approach with a case study design. Data were obtained through observation, semi-structured interviews, and documentation, then analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results showed that the implementation of the educational game was carried out through a group game of guessing the hijaiyah letters using simple media such as letter cards, a whiteboard, and sign language. The implementation of this game was able to increase student participation, motivation, concentration, and social interaction during the learning process. In addition, the educational game helped deaf children recognize the hijaiyah letters, improved memory, and facilitated understanding of the material through a visual approach that suited their learning needs. Although there are differences in abilities and needs for assistance for each student, the use of educational games has been proven to create a more active, collaborative, and enjoyable learning atmosphere. Thus, educational games can be an effective alternative learning medium to support Islamic Religious Education for deaf children.